2019
DOI: 10.1104/pp.18.01353
|View full text |Cite
|
Sign up to set email alerts
|

Direct Comparison of Leaf Plasmodesma Structure and Function in Relation to Phloem-Loading Type

Abstract: The export of photosynthetically produced sugars from leaves depends on plasmodesmatal transport of sugar molecules from mesophyll to phloem. Traditionally, the density of plasmodesmata (PD) along this phloem-loading pathway has been used as a defining feature of different phloem-loading types, with species proposed to have either many or few PD between the phloem and surrounding cells of the leaf. However, quantitative determination of PD density has rarely been performed. Moreover, the structure of PD has no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The PD channels represent the main pathway for intercellular exchange of molecules (Bayer et al, 2014;Otero et al, 2016) and it has been known for many years that they are exploited by plant viruses for their cell-to-cell movement (Tomenius et al, 1987;Wolf et al, 1989;Heinlein, 2015b). The PD channel has a cytoplasmic space delimited by the plasma membrane (PM) and an axial appressed tubule of endoplasmic reticulum (ER) termed 'desmotubule', therefore looking like a system of two membrane tubes inserted one into the other (Bell & Oparka, 2011;Liesche et al, 2019). The PM and desmotubule membranes are located close to each other, at a distance of c. 10-15 nm, and the cytoplasmic, intermembrane space contains spoke-like, presumably proteinaceous, elements that emanate from the desmotubule and link the two membranes (Roberts & Oparka, 2003;Petit et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The PD channels represent the main pathway for intercellular exchange of molecules (Bayer et al, 2014;Otero et al, 2016) and it has been known for many years that they are exploited by plant viruses for their cell-to-cell movement (Tomenius et al, 1987;Wolf et al, 1989;Heinlein, 2015b). The PD channel has a cytoplasmic space delimited by the plasma membrane (PM) and an axial appressed tubule of endoplasmic reticulum (ER) termed 'desmotubule', therefore looking like a system of two membrane tubes inserted one into the other (Bell & Oparka, 2011;Liesche et al, 2019). The PM and desmotubule membranes are located close to each other, at a distance of c. 10-15 nm, and the cytoplasmic, intermembrane space contains spoke-like, presumably proteinaceous, elements that emanate from the desmotubule and link the two membranes (Roberts & Oparka, 2003;Petit et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The sections were then observed and imaged with a transmission electron microscope (TECNAI G2, FEI, USA). The plasmodesma diameters were measured at the neck region via the TEM Imaging & Analysis software (FEI, USA; Schindelin et al , 2012 ; Liesche et al , 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The second way to change the intercellular conductivity is the modification of Pd structure when a transition from primary to secondary Pd occurs. The study of the sink-source transition in tobacco leaves has shown how this mechanism works [28] when a large number of simple primary Pd are lost and the contents of branched secondary Pd increase [26,40].…”
Section: Mechanisms Of Pdap Participation In Intercellular Cytoplasmimentioning
confidence: 99%
“…Pd provide a controlled symplastic exchange of both low molecular weight compounds and larger molecules, such as signaling molecules, transcription factors, non-cell-autonomous plant proteins [17,18], small regulatory RNAs and messenger RNAs [19,20], between plant cells, allowing general reactions in their growth processes and in response to stressful environmental factors [21][22][23]. Through Pd and phloem, photosynthesis products from the mesophyll of source leaves are exported to sink leaves and the plant growth point [24][25][26]. Sucrose, as a primary carbohydrate transported long distances in many plant species, is loaded into the phloem and unloaded into distal sink tissues.…”
Section: Introductionmentioning
confidence: 99%